AN IMPROVEMENT ON AN APPROXIMATE FUNCTIONAL EQUATION FOR e^iÎ¸ H(1/2+it) - PUNNIAKRISHNAN, K. (International Journal of Mathematical Archive, 2018)
In this paper the approximate functional equation for Â due to E.C. Titchmarash has been analysed. A minor simplification of the above equation has been obtained. New forms of the above equation in a similar way are derived. Â